COMPREHENSIVE ANALYSIS OF IRAN’S POTENTIAL PERMANENT MEMBERSHIP IN THE SHANGHAI COOPERATION ORGANIZATION - Muhammad Ilyas Khan; Muhammad Yousaf khan; Farid Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
The Shanghai Cooperation Organization (SCO), a regional intergovernmental organization, is crucial for regional security, economic cooperation, and geopolitical dynamics. Iran’s accession to the SCO is seen as a step to strengthen regional ties and compete economically. After gaining permanent membership in the grouping due to its geographical proximity and importance as a regional player, the country now holds significant influence. Iran has seen the SCO as an alternative venue to address security challenges, economic integration, and nuclear protection. The study uses a qualitative research design, examining Iran’s pursuit of permanent membership and its impact on political, economic, scientific, technological, energy, and environmental issues. Iran’s elevation to permanent membership status in the SCO marks a significant development in regional geopolitics, reflecting its strategic imperative to diversify alliances and enhance regional cooperation. China and Russia have the leading status in the organization, and Iran’s membership has become a triangular partnership in the grouping with a common adversary, the United States. Iran can maximize the benefits of its membership and positively contribute to regional stability and prosperity by actively engaging in SCO activities and initiatives.